1993
DOI: 10.1108/10610429310046689
|View full text |Cite
|
Sign up to set email alerts
|

Brand Equity in the Business‐to‐Business Sector

Abstract: Posits a stagewise learning process involved in the building of brand equity: brand birth; the creation of brand awareness and associations; the building of quality and value perceptions; the emergence of brand loyalty; and the launching of brand extensions. Also reports on an empirical study which explored the evolution, existence and extensibility of brand equity in a particular business‐to‐business market. Concludes with practical implications for managers in business‐to‐business product or service firms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 3 publications
3
144
0
3
Order By: Relevance
“…Industrial buyers are more likely to seek expert advice or technical advice both from within and outside the firm. For example, architects and engineers are influential in the purchase decision to buy electrical switches (Gordon et al, 1993). To create brand awareness for the B2B brand, personal selling is vital (Bendixen et al, 2004).…”
Section: B2b Brand Marketing Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Industrial buyers are more likely to seek expert advice or technical advice both from within and outside the firm. For example, architects and engineers are influential in the purchase decision to buy electrical switches (Gordon et al, 1993). To create brand awareness for the B2B brand, personal selling is vital (Bendixen et al, 2004).…”
Section: B2b Brand Marketing Programmentioning
confidence: 99%
“…In the study of Gordon et al (1993), electrical contractors ranked brands fourth out of six factors that influence their choice of distributors for electrical switches. In this research the supplier had stopped direct customer sales, so the task of creating brand awareness (providing sales leaflets) was left to distributors.…”
Section: B2b Brand Marketing Programmentioning
confidence: 99%
“…This paper measures attitudinal brand loyalty in a business services context rather than a consumer setting. Previous research has identified that branding is an important issue in business, [22][23][24][25] and loyalty holds a great deal of relevance for services, both consumer and business. [26][27][28] …”
Section: Attitudinal Loyaltymentioning
confidence: 99%
“…Dissemination of corporate brand names and logos is central for many companies to convey information about their quality, people, skills, and behavior (Akerlof 1970;Gordon, Calantone, and di Benedetto 1993;Homburg, Klarmann, and Schmitt ;Kotler and Pfoertsch 2007). In fact, building corporate brand awareness without developing a more comprehensive brand identity is the focal B2B branding strategy for many firms (Homburg, Klarmann, and Schmitt 2010).…”
Section: Corporate Brand Investments and Price Premiumsmentioning
confidence: 99%